COPs and 'robbers?' Better understanding community energy and toward a Communities of Place then Interest approach. (October 2022) - Walker, Chad; Poelzer, Greg; Leonhardt, Renata; Noble, Bram; Hoicka, Christina
Abstract: Following its growing popularity in practice, social scientists have turned their attention to a greater understanding of community energy (CE). Beginning with Walker and Devine-Wright's 2008 framework, researchers have consistently been critical about the use of the term – especially when doing so to further powerful, non-local interests. Unpacking what the 'community' in CE means has been of particular interest and a few recent studies have shown that different sets of outcomes largely depend on what definition is used. At the same time, many in this literature have pointed to the value of geographic concepts – for example, characterizing communities as either Communities of Place (COPs) or Communities of Interest (COIs). Yet these two characterizations have largely remained in the background, rather than the focus, of CE studies. Here, we attempt to add conceptual clarity to the term CE by tracing the benefits of COP, COI, and hybrid-based (i.e. a combination) projects. We do so through a qualitative content analysis of 133 research articles from more than 30 countries published from 2010 to 2020. The benefits of COP-based CE (i.e. greater social acceptance, creating 'energy citizens') are mostly associated with popular descriptions of CE, while the benefits of COI-based CE were cited as those that address the perceived shortcomings of COP-based CE. Finally, it might be the hybrid approach that can effectively marry both COPs and COIs. More specifically, we find that the order of this 'marriage' matters and recommend that approaches centered around Communities of Place, then Interest (COPTI) should be prioritized. The paper closes with a discussion of some possible next steps, in terms of social scientific research and the practice of CE.